Review of Islamic Economic Law on the Handling of Problem Financing at PT Bank Syariah Indonesia Samarinda Bhayangkara Branch - Dwi Eko Rhomadon, Muhammad; Ardyansah, Muhammad Rafi (Ghaly: Journal of Islamic Economic Law, 2025)
This research discusses the review of muamalah fiqh on the handling of problem financing at PT Bank Syariah Indonesia, Tbk. Samarinda Branch. Non-performing financing is a major challenge in Islamic banking that requires resolution in accordance with sharia principles. This research aims to identify the factors that cause non-performing financing and analyse the settlement mechanism based on the perspective of fiqh muamalah. The research method used is qualitative with a descriptive-analytical approach. The results show that the main causes of non-performing financing include internal factors, such as negligence in credit analysis, as well as external factors, such as economic conditions and the inability of customers to fulfil their obligations. In its settlement, Bank Syariah Indonesia applies several strategies, such as restructuring, rescheduling, and settlement through appropriate sharia contracts. From the perspective of muamalah fiqh, these measures are acceptable as long as they do not contain elements of usury, gharar, and dzalim. This research is expected to serve as a reference in improving the effectiveness of financing risk management inIslamic banks to remain in accordance with sharia principles.